2001
DOI: 10.1111/j.1651-2227.2001.tb01606.x
|View full text |Cite
|
Sign up to set email alerts
|

Hearing impairment in preterm very low birthweight babies detected at term by brainstem auditory evoked responses

Abstract: Seventy preterm babies who were born with a birthweight <1500 g were studied with brainstem auditory evoked responses (BAER) at 37‐42 wk of postconceptional age. The data were compared with those of normal term neonates to determine the prevalence of hearing impairment in preterm very low birthweight (VLBW) babies when they reached term. The BAER was recorded with click stimuli at 21 s−1. Wave I and V latencies increased significantly (ANOVA p < 0.01 and 0.001). I‐V and III‐V intervals also increased sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0
5

Year Published

2006
2006
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 17 publications
3
10
0
5
Order By: Relevance
“…45 In our cohort, 1.5% of the VLBW infants were found to have abnormal ABR results-that is, prolonged BTT-despite normal ABR thresholds and normal TEOAEs. Similar findings were reported by Jiang et al 46 This finding supports routine implementation of TEOAE as a quick, easily performed first stage screening tool before discharge from What is already known on this topic N VLBW infants are at increased risk of sensory-neural hearing loss What this study adds N This study shows a low prevalence of sensory-neural hearing loss in a group of VLBW infants, which needs confirmation N The rate of conductive hearing impairment was high as expected hospital (thus reaching all babies), but a diagnostic ABR should also be routinely performed in this population.…”
Section: Discussionsupporting
confidence: 92%
“…45 In our cohort, 1.5% of the VLBW infants were found to have abnormal ABR results-that is, prolonged BTT-despite normal ABR thresholds and normal TEOAEs. Similar findings were reported by Jiang et al 46 This finding supports routine implementation of TEOAE as a quick, easily performed first stage screening tool before discharge from What is already known on this topic N VLBW infants are at increased risk of sensory-neural hearing loss What this study adds N This study shows a low prevalence of sensory-neural hearing loss in a group of VLBW infants, which needs confirmation N The rate of conductive hearing impairment was high as expected hospital (thus reaching all babies), but a diagnostic ABR should also be routinely performed in this population.…”
Section: Discussionsupporting
confidence: 92%
“…Jiang et al [7] found an incidence of abnormal central ABR component in 17% of preterm very low birth weight infants. Although the populations differ with respect to birth weight and failing neonatal hearing screening, the prevalence of prolonged I–V interval as a measure of abnormal central component concur.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported to be increased in preterm infants as compared to term infants [79]. The I–V interval shows an age-dependent decline up to about 2 years of age [1012].…”
Section: Introductionmentioning
confidence: 99%
“…This was seen with both sensory neuronal and conductive deafness and the numbers of infants with deafness not corrected with aids increased from two to five. Recent studies have shown that there has been a decrease in sensory neuronal deafness in neonatal intensive care unit graduates overall 25. Studies of VLBW infants, however, continue to show a higher incidence of hearing impairments which are probably multifactorial in origin.…”
Section: Discussionmentioning
confidence: 99%